Biogas Effectiveness Test from Household Waste (Vegetable Waste) with Cow Dung Starter and EM4 - Mukti, Rizka Nurfarida; Salsabilla, Adinda; Muamar, Aina Salsabila; Prima, Eka Cahya; Hana, Muhammad Nurul (Universitas Pendidikan Indonesia (UPI), 2021)
This research focuses on finding solutions to get around the energy crisis. This study aimed to know the effectiveness of household waste (vegetable waste) biogas using a starter mixture of cow dung and EM4. What is new from this research is the use of household waste as biogas energy. The research method used is the study of literature from various journals and articles, accurate and reliable. Various journals and conceptual articles were obtained from google scholar and the liputan6.com website page. From the experimental results, the more the composition of vegetable waste, the higher the pressure, but the less the flame. Based on the research results, it can be concluded that biogas made from vegetable waste alone is quite effective to be used as a solution to the energy crisis problem (to replace LPJ gas, to be precise) because of the large amount of methane produced. However, if we are want to be an innovation for successful village development, biogas from household waste (vegetable waste) can be used by adding cow dung as the main ingredient. So that methane is produced in large quantities according to the amount of material used.